Developing halal built-in work system for manufacturing of pharmaceuticals / Suraiya Abdul Rahman - Abdul Rahman, Suraiya (2023)
Halal built-in is a systematic approach which integrates the requirement of halal in all aspect of manufacturing. However, the Malaysian Standard in Halal Pharmaceuticals, and guidelines for halal certification in Malaysia are diverse and missing an overview of an efficient work system framework. Furthermore, the standards and guidelines emphasise more on the technical requirements, lacking emphasis on values, spiritual or conscience elements. This qualitative case study was conducted to 1) explore the current practices in implementing halal built-in system adopted by the Malaysian halal industry stakeholders for manufacturing halal pharmaceuticals, 2) elucidate the references that have been used by the halal industry stakeholders as guidance for production of Sharīʿah compliant pharmaceuticals 3) discover the challenges that need to be overcome to successfully implement a halal built-in system 4) propose a framework of halal pharmaceutical built-in work system. Data were collected through face-to-face semi-structured interview with experts, selected through purposive sampling and divided into four groups, namely the fiqh expert, JAKIM officers, Ministry of Health regulators (MoH) and pharmaceutical industry players. Three participants were interviewed from each group. The interview protocol was developed based on Steven Alter’s Work System Method (WSM) consisting of nine (9) elements. The data from transcribed interviews were assessed using thematic analysis. Outcome of the study showed that, with regards to the current practice of halal built-in work system implementation, the four groups of participants seem to have differing depth and polarised knowledge of the current practice in halal built-in system. Fiqh experts were polarised towards the upstream elements such as Sharīʿah and fatwa matters. Instead, MoH participants’ responses were mostly skewed towards the downstream of the halal built-in, focusing more on the end user’s, such as patients’ demand for halal medicine, doctors’ concern on medication non-compliance, and MoH’s halal logo policy. JAKIM and the industry participants showed more comprehensive knowledge on halal built-in system, since they were actively involved.